Táticas reprodutivas e ocorrência parasitária de isópodos em carapeba, Diapterus rhombeus (Cuvier, 1829), no Rio Grande do Norte, Brasil - Freitas, Maria Daniana Felix de (Universidade Federal Rural do Semi-Árido, 2017)
Diapterus rhombeus is a fish of coastal and estuarine water that can be found throughout the Western Atlantic, from the Gulf of Mexico to Brazil. As it is a peidxe of great abundance it is important to have knowledge about the reproductive and parasitological biology of the species. With this, the objective of this study was to verify the main tactics that compose the reproductive strategy and the condition factor of D. rhombeus and the occurrence of isopod ectoparasites. The study was carried out in marine waters in the Northwest of the Atlantic Ocean (4º 50'57 ''S and 3751'36''W), more precisely in the coast of Areia Branca, RN, Brazil. A total of 298 individuals of the species were captured, in which in the study of their reproductive tactics it was identified that the individuals presented total weight ranges from 51.4g to 220.5g and a total length of 150mm to 245mm, where females were always found to be larger range of total length than males. In the analysis of weight and length both sexes presented a negative allometric growth, that is, the individuals had greater increase in length than in weight. Individuals presented a 1.8M: 1F sex ratio throughout the study. Four stages of gonadal maturation were identified macroscopically: immature, maturing, mature and emptied and microscopic study with histological analysis showed oocyte and sperm development within gonads at each stage of maturation. The length at which individuals entered first maturation was calculated to be 160 mm in total length. The gonadosomatic index (IGS) showed higher peaks for both males and females in November, December and January, indicating that the spawning season occurs soon after this period. The absolute fecundity was 16,313 oocytes and indicated that the females had a synchronous reproductive development in two groups. In the study of condition factor (K) higher peaks were shown shortly after the spawning season, indicating that the greater well-being of the individuals occurs in this period. The parasitic study showed that the species is parasitized by Cymothoa excisa, an isopod parasite that was found inhabiting the oral cavity of the individuals, presenting parasitic indexes with prevalence of 7.38%, mean intensity of 1.18 and average abundance of 0.09. In the present work, D. rhombeus individuals possess reproductive tactics that identify the species as a fish seasonal strategist and that the species can be considered as a new host of the C. excisa isotope ectoparasite
Reproductive tactics and parasitary occurrence of isopods in carapeba, Diapterus rhombeus (Cuvier, 1829), in Rio Grande do Norte, Brazil
Keywords: Estratégia reprodutiva; Reprodução de peixes; Ectoparasitos em peixes marinhos; Gerreidea; Reproductive strategy; Fish reproduction; Ectoparasites in marine fish; Gerreidea; CIENCIAS AGRARIAS::ZOOTECNIA